Relationship between short stature at 3 years old and height, weight, and body mass index changes for 6 years after birth: a retrospective, nationwide, population-based study of children born 2011-2014 in Korea - Seo Jung Kim; Ju Hyun Jin; In Hyuk Chung (Korean Society of Pediatric Endocrinology, 2023)
Purpose Height at 3 years of age, when catch-up growth based on birth history is completed, is considered a major prognostic factor for predicting short stature, underweight, and growth faltering. However, too few large-scale studies have followed and analyzed height, weight, and body mass index (BMI) changes in children whose stature was short at 3 years of age. This study followed and compared the growth parameters (height, weight, and BMI) of children with short stature at 3 years of age and children with nonshort stature at 3 years of age for 6 years after birth using nationwide, population-based data. Methods We retrospectively analyzed physical measurement data from the National Health Screening Program for Infants and Children for people born in 2011-2014 in Korea and followed to 2020. The data were provided by the National Health Insurance Service's customized data service. Growth parameters were compared using chi-square tests, Student t-tests, analyses of variance, and linear regressions. Results Among 210,902 enrolled participants, 759 (0.4%) and 210,143 (99.6%) were in the short stature at 3 years group and the nonshort stature at 3 years group, respectively. In both sexes, height, weight, and BMI for 6 years after birth were significantly higher in the nonshort stature at 3 years group than in the short stature at 3 years group (P<0.0001). The BMI rebound was observed later than the standard period in the short stature at 3 years group. Conclusions Early intervention and close follow-up are necessary to prevent persistent short stature and growth faltering in children with short stature at 3 years of age.